Public satisfaction with the Ethiopian healthcare system: a mixed methods approach - Getahun, Genanew Kassie; Demissie, Bemnet Dires; Baraki, Semere Gebremariam (Frontiers in Public Health, 2024)
The public's satisfaction with the healthcare system of Ethiopia is a crucial but unanswered question. This is an essential issue since recent trends indicate that the demographic and epidemiological makeup of the population is changing. Therefore, the aim of this study was to assess the overall satisfaction of the public with the Ethiopian healthcare system in Addis Ababa, Ethiopia, in 2022.A community-based convergent parallel mixed-method study was conducted.Bivariable and multivariable logistic regression analysis were used to determine the factors associated with public satisfaction. A 95% confidence interval along with a p-value of less than 0.05 was deemed sufficient to declare a significant association. For the qualitative component we used thematic analysis.The vast majority, 77.2% (95% CI: 76.18-78.22%) of respondents were dissatisfied with the existing health-care system. Moreover, Community Based Health Insurance (CBHI) enrolment 2.35 (95% CI: 1.32-4.19), poor linkage to social capital 0.46 (95% CI: 0.25-0.83), poor access to healthcare services 0.39 (95% CI: 0.21-0.76), and absence of satisfactory responses to complaints 0.11 (95% CI: 0.04-0.27) were significantly associated with public dissatisfaction.The public satisfaction with the Ethiopian healthcare system was low.Furthermore, it was affected by different factors including enrollment in the CBHI, linkage to social capital, accessibility to healthcare, and satisfactory response. Therefore, the government of Ethiopia should enhance CBHI coverage, access, and an immediate compliant solution strategy.